2005
DOI: 10.1186/1476-511x-4-10
|View full text |Cite
|
Sign up to set email alerts
|

Role of cholesterol in parasitic infections

Abstract: The requirement of cholesterol for internalization of eukaryotic pathogens like protozoa (Leishmaniasis, Malaria and Toxoplasmosis) and the exchange of cholesterol along with other metabolites during reproduction in Schistosomes (helminths) under variable circumstances are poorly understood. In patients infected with some other helminthes, alterations in the lipid profile have been observed. Also, the mechanisms involved in lipid changes especially in membrane proteins related to parasite infections remain unc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
57
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 104 publications
(65 citation statements)
references
References 62 publications
4
57
0
Order By: Relevance
“…Increasing evidence suggests that host lipids are manipulated by, and allocated to pathogens. Helminths may regulate host lipid metabolism by stimulating a decrease in total cholesterol levels [107], particularly low-density lipoprotein (LDL) and Apolipoprotein B [132]. Several mechanisms may account for these decreases.…”
Section: Cardio-metabolic Protective Effects Of Helminth Infectionmentioning
confidence: 99%
See 1 more Smart Citation
“…Increasing evidence suggests that host lipids are manipulated by, and allocated to pathogens. Helminths may regulate host lipid metabolism by stimulating a decrease in total cholesterol levels [107], particularly low-density lipoprotein (LDL) and Apolipoprotein B [132]. Several mechanisms may account for these decreases.…”
Section: Cardio-metabolic Protective Effects Of Helminth Infectionmentioning
confidence: 99%
“…Helminths and protozoans (e.g. giardia) cannot synthesize their own lipids, and so consume and metabolize host lipids to generate phospholipid membranes [132], exploiting the host lipidome for their own survival and reproduction [84, 134, 135]. Other pathogens, including bacteria such as H. pylori and M. tuberculosis also exploit host lipids for their own growth, maintenance and signaling [136].…”
Section: Cardio-metabolic Protective Effects Of Helminth Infectionmentioning
confidence: 99%
“…In addition to its role in providing energy for various physiological processes, lipid metabolism has been implicated in infectious and parasitic diseases (19). Lipid carrier proteins have been reported to reduce the toxicity of lipopolysaccharide in both invertebrates (20,21) and mammals (22,23).…”
Section: Lipophorin (Lp)mentioning
confidence: 99%
“…Bansal et al 5. reported that most of the parasites induce significant changes in lipid profiles in patients having active infections.…”
Section: Introductionmentioning
confidence: 99%